2021
DOI: 10.1152/japplphysiol.00553.2020
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenergic agonist salbutamol augments hypertrophy in MHCIIa fibers and sprint mean power output but not muscle force during 11 weeks of resistance training in young men

Abstract: In this study, we examined the effect of beta2-agonist salbutamol at oral doses during a period of resistance training on sprint performance, quadriceps contractile function, skeletal muscle hypertrophy, fiber-type composition, maximal activity of enzymes of importance for anaerobic energy turnover, and sarcoplasmic reticulum Ca2+-handling in young men. Twenty-six men (23±2 years;mean±SD) were randomized to daily intake of oral salbutamol (16 mg/d;RES+SAL) or placebo (RES) during 11 weeks full-body resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 61 publications
(67 reference statements)
1
23
0
Order By: Relevance
“…The endurance-training group receiving terbutaline experienced a weight loss of 1.9 kg compared with placebo, whereas the resistance-training group receiving terbutaline had a 1 kg greater gain of muscle mass than placebo but not a greater reduction of fat mass (Jessen et al 2018). The latter observation corresponds with studies showing an additive effect of salbutamol on muscle power and hypertrophy in young men subjected to a period of resistance training (Caruso et al 2005;Jessen et al 2021). Hence, beta 2 -agonists may exert some beneficial effects on body composition when taken concomitantly with training as demonstrated for terbutaline (Fig.…”
Section: Interaction Between Exercise and Beta 2 -Agonistssupporting
confidence: 58%
See 1 more Smart Citation
“…The endurance-training group receiving terbutaline experienced a weight loss of 1.9 kg compared with placebo, whereas the resistance-training group receiving terbutaline had a 1 kg greater gain of muscle mass than placebo but not a greater reduction of fat mass (Jessen et al 2018). The latter observation corresponds with studies showing an additive effect of salbutamol on muscle power and hypertrophy in young men subjected to a period of resistance training (Caruso et al 2005;Jessen et al 2021). Hence, beta 2 -agonists may exert some beneficial effects on body composition when taken concomitantly with training as demonstrated for terbutaline (Fig.…”
Section: Interaction Between Exercise and Beta 2 -Agonistssupporting
confidence: 58%
“…2005; Jessen et al . 2021). Hence, beta 2 ‐agonists may exert some beneficial effects on body composition when taken concomitantly with training as demonstrated for terbutaline (Fig.…”
Section: Interaction Between Exercise and Beta2‐agonistsmentioning
confidence: 99%
“…After short-term oral salbutamol administration, maximal anaerobic power but not capacity was improved, irrespective of the gender or training status, with no change in body composition (Le Panse et al, 2005 , 2006 ). Other studies performed only in men showed various results after salbutamol or terbutaline inhalation or intake, with change or no change in aerobic (Collomp et al, 2000 ) and anaerobic performances, coupled or not to anabolic effects (Hostrup et al, 2014 ; Jessen et al, 2021 ). Women may have greater sensitivity to beta-2 receptor stimulation (Kneale et al, 2000 ), but in view of the same TUE prevalence for beta-2 agonists in female and male athletes (Vernec and Healy, 2020 ) and the lack of studies on the pharmacokinetics and the ergogenic, physiological, and psychological terbutaline effects in women, it is difficult to speculate on the higher number of terbutaline cases found in female athletes.…”
Section: Discussionmentioning
confidence: 99%
“…The study employed a randomized double‐blinded placebo‐controlled crossover design and is part of a larger project investigating beta 2 ‐adrenergic effects on skeletal muscle hypertrophy and metabolism induced by selective beta 2 ‐agonist. A part pertaining to beta 2 ‐adrenergic‐induced changes in muscle protein turnover rates, 35 glucose metabolism, 36 and hypertrophy 37 have been described elsewhere. The outcome measures for the present part are arterial and venous IL‐6 concentrations, a‐v IL‐6 difference, IL‐6 release, and mRNA levels of IL‐6 and TNF‐α.…”
Section: Methodsmentioning
confidence: 99%